Prediction of RC beams failure load using non-linear finite element analysis - Aswin, M. (Research India Publications, 2015)
This paper presents the results of non-liner finite element analysis using commercial package of VecTor2 performed on different types of RC beams. Three types of RC beams were considered from available literatures which are; simply supported RC deep beams with web openings, continuous RC deep beams with web openings and simply supported RC dapped-end beams. Two responses were analyzed and compared to the experimental results which are failure load and failure mode. It has been found that the ratio of the analytical failure load to the experimental failure load very close to 1. In addition, the experimental failure modes were depicted accurately. Â© Research India Publications.